Primary renal leiomyosarcoma arising from renal vein: A case report of rare entity with review of literature - Reetu Kundu; Mahesh Chandra; Rajpal Singh Punia; Purnima Aggarwal (Indian Journal of Medical and Paediatric Oncology)
Primary renal sarcomas are extremely rare neoplasms accounting for about 1% of all malignant renal neoplasms. Among all the sarcomas of kidney, leiomyosarcoma is the most common histotype. The histogenesis of these tumors is unclear, and presumably, they arise either from renal capsule or smooth muscle of renal vessels or renal pelvis. We report a case of a 65-year-old woman, who presented with intermittent abdominal pain for 1 year. The correct diagnosis was established only after the histopathological analysis of the resected specimen. The poor prognosis borne by these tumors mandates a thorough evaluation of all renal masses with unusual gross and histomorphology.